The effect of Ginkgo biloba EGb 761 on intestinal anastomotic healing in rats with ischemia-reperfusion induced in the lower extremities - Basim, Serdar; Basim, Pelin; Demiray, Okan (Journal of Surgery and Medicine, 2021)
Background/Aim: Remote ischemia-reperfusion (I-R) injury for anastomotic healing is a newly identified risk factor and there is a wide array of studies being conducted. This study aimed to reveal the negative effects of lower I-R on the colonic anastomotic healing process and examine the effects of Ginkgo biloba EGb 761 treatment, a platelet activating factor (PAF) antagonist, on anastomotic healing through the inhibition of pathological mechanisms of mediators causing these negative effects. Methods: Thirty-six Wistar-Albino rats were divided into sham, I-R and I-R+EGb 761 groups, each consisting of 12 rats. In the subjects in the sham group, an end-to-end anastomosis was performed by transecting the descending colon following midline laparotomy. In the I-R group, unilateral lower extremity ischemia was created by occluding the femoral artery and collaterals using a tourniquet from the most proximal segment of the left extremity. Then, the descending colon was transected, anastomosis was performed, and reperfusion was created by a tourniquet application at the 30th minute of ischemia. Different from the I-R (control) group, the subjects in the I-R+EGb 761 group were given two equal doses of 64 mg/kg/d Ginkgo biloba EGb 761 by the orogastric route until 10 days after surgery. After all subjects were sacrificed on the 10th day of surgery, the descending colon segment containing the anastomosis area was resected and samples were taken for bursting pressure and hydroxyproline measurements. Results: In the I-R group, anastomotic bursting pressure and perianastomotic hydroxyproline values were significantly lower compared to the sham group and the I-R+EGb 761 group. However, there was no statistically significant difference in these parameters between the sham and the I-R+EGb 761 groups. Conclusion: Colonic anastomotic bursting pressure and peri-anastomotic hydroxyproline values in the sham group were significantly decreased by lower extremity I-R, and this change was prevented with the use of EGb 761.